2022
DOI: 10.3390/antiox11112202
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mitochondrial Metabolism to Reverse Radioresistance: An Alternative to Glucose Metabolism

Abstract: Radiotherapy failure and poor tumor prognosis are primarily attributed to radioresistance. Improving the curative effect of radiotherapy and delaying cancer progression have become difficult problems for clinicians. Glucose metabolism has long been regarded as the main metabolic process by which tumor cells meet their bioenergetic and anabolic needs, with the complex interactions between the mitochondria and tumors being ignored. This misconception was not dispelled until the early 2000s; however, the cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 147 publications
0
15
0
Order By: Relevance
“…Consequently, metabolic changes induced by radiation may correlate with the radiation sensitivity of tumor cells. Studies have shown a close association between glucose metabolism and radioresistance [ 30 ]. Radioresistant tumor cells often exhibit increased glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, metabolic changes induced by radiation may correlate with the radiation sensitivity of tumor cells. Studies have shown a close association between glucose metabolism and radioresistance [ 30 ]. Radioresistant tumor cells often exhibit increased glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of cellular energy and redox status via mitochondrial metabolism, a process known as mitochondrial metabolic reprogramming, has been shown to be associated with cancer progression [ 61 , 62 ]. As a result, targeting mitochondria by inhibiting mitochondrial complexes presents a novel therapeutic strategy for cancer [ 63 , 64 ]. Our in vitro data showed that IL-1RA overexpression increased the rate of mitochondrial oxidative metabolism and inhibition of mitochondrial electron transfer complexes, including the use of conventional compound inhibitors (e.g., metformin, phenformin, rotenone, or antimycin A [ 39 , 65 ]) and novel peptide inhibitors (e.g., CT20 [ 66 ] or MITOx20 [ 67 ]), suppressed IL-1RA-promoted malignant behaviors of OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, SOD1 overexpression confers radioresistance in human glioma cells by suppressing irradiation-induced late ROS accumulation. These contradictory results may be due to the dual role of ROS in which the difference in ROS levels is dominant ( Bian et al, 2022b ). The copper chaperone for COX17, which is located in the cytoplasm and mitochondrial membrane space (IMS), is another copper metallochaperone involved in electron transfer in the oxidative respiratory chains ( Lyons et al, 2012 ).…”
Section: Regulation Of Copper Homeostasis In Mammalian Cellsmentioning
confidence: 99%